1998
DOI: 10.1007/s004360050409
|View full text |Cite
|
Sign up to set email alerts
|

Compared vectorial transmissibility of pure and mixed clonal genotypes of Trypanosoma cruzi in Triatoma infestans

Abstract: A total of 15 mixtures involving 9 different stocks attributed to the 19/20, 32 and 39 major clonal genotypes of Trypanosoma cruzi were used to infect third-instar nymphs of Triatoma infestans via an artificial feeding device. Three biological parameters were considered: (1) the percentage of infected insects (%II), (2) the number of flagellates per insect (NFI), and (3) the percentage of trypomastigotes per insect (%DIF). Genetic characterization by both multilocus enzyme electrophoresis (MLEE) and random amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 17 publications
(13 reference statements)
3
26
0
Order By: Relevance
“…58,60 Moreover, under long periods of starvation, 99.5% of T. cruzi in the rectum of an infected triatomine can be killed, and T. cruzi population density in the small intestine and rectum is reduced. 61 Thus, adults probably undergo this process several times during their lifetime, which filters many genotypes and retains and proliferates those genotypes that are more resistant to adverse situations, both from the vector, such as trypanolytic compounds, digestive enzymes, and lectins, 62 and environmental ones, such as resident bacteria in the gut, temperature variation, 62 and resource shortage.…”
Section: Discussionmentioning
confidence: 99%
“…58,60 Moreover, under long periods of starvation, 99.5% of T. cruzi in the rectum of an infected triatomine can be killed, and T. cruzi population density in the small intestine and rectum is reduced. 61 Thus, adults probably undergo this process several times during their lifetime, which filters many genotypes and retains and proliferates those genotypes that are more resistant to adverse situations, both from the vector, such as trypanolytic compounds, digestive enzymes, and lectins, 62 and environmental ones, such as resident bacteria in the gut, temperature variation, 62 and resource shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Our group verified that in mixed infections, interactions between populations of T. cruzi may occur, resulting in important changes in the biological characteristics of the parasite and the evolution of the infection (12,25,32). Moreover, the importance of mixed infections in the epidemiology of Chagas' disease (8,35) and the evidence that they may result in significant alterations in the host-parasite relationship motivated the studies on the efficacy of chemotherapy in dual infections.…”
Section: Discussionmentioning
confidence: 80%
“…Interactions between T. cruzi clonal stocks of different genotypes suggesting reciprocal stimulation or inhibition were already demonstrated in experimental infections of Triatoma infestans (12,32) and mice (25). Those authors observed that clones with a low ability to develop in invertebrate or vertebrate hosts in monoclonal infections were able to multiply and to remain in mixed infections (19 or 20 ϩ 32) at levels even higher than that of the most virulent clone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing two fresh isolates, both originating from T. vitticeps, one isolate infected 61% and the other one 39% of T. infestans (Kollien et al 1998). Clone or strain specificities are indicated not only by different numbers of parasites in the gut but also by different percentages of metacyclic trypomastigotes (e.g., Perlowagora-Szumlewicz et al 1990;Perlowagora-Szumlewicz and Moreira 1994;Alvarenga and Bronfen 1997;Pinto et al 1998;Lana et al 1998;Lima et al 1999). Using two T. cruzi strains from the same locality and T. infestans also originating from there, the number of metacyclics differed strongly .…”
Section: Disadvantages Of Xenodiagnosis Of Chagas Disease: Sensitivitymentioning
confidence: 99%